Death Pathways Associated with Photodynamic Therapy. (4th May 2021) - Kessel, David
Abstract: This report describes studies involving ER vs. lysosomal targeting and is designed to assess the initiation of different death pathways as a function of subcellular targeting and PDT dose. Photodamage directed at mitochondria or lysosomes initiates apoptosis, a death pathway generally considered to be irreversible. Photodamage that involves the ER can lead to another death pathway termed paraptosis. This does not involve caspase activation, can eradicate cell types with impaired apoptosis; at high levels of irradiation, apoptosis and necrosis were observed. Autophagy has a cytoprotective function unless lysosomes are targeted; loss of lysosomal integrity can interfere with the autophagic recycling processes. Abstract : Pathways for photokilling involving lysosomal (A) or ER (B) photodamage. The effect of autophagy can be observed as a shoulder on the log dose–response curve in (B).